The role of zyxin in signal transduction and its relationship with diseases - Wu, Zelan; Wu, Daiqin; Zhong, Qin; Zou, Xue; Liu, Zhongjing; Long, Hehua; Wei, Jing; Li, Xia; Dai, Fangjie (Frontiers in Molecular Biosciences, 2024)
This review highlighted the pivotal role of zyxin, an essential cell focal adhesions protein, in cellular biology and various diseases. Zyxin can orchestrate the restructuring and dynamic alterations of the cellular cytoskeleton, which is involved in cell proliferation, adhesion, motility, and gene transcription. Aberrant zyxin expression is closely correlated with tumor cell activity and cardiac function in both tumorigenesis and cardiovascular diseases. Moreover, in fibrotic and inflammatory conditions, zyxin can modulate cellular functions and inflammatory responses. Therefore, a comprehensive understanding of zyxin is crucial for deciphering signal transduction networks and disease pathogenesis. Investigating its role in diseases holds promise for novel avenues in early diagnosis and therapeutic strategies. Nevertheless, targeting zyxin as a therapeutic focal point presents challenges in terms of specificity, safety, drug delivery, and resistance. Nonetheless, in-depth studies on zyxin and the application of precision medicine could offer new possibilities for personalized treatment modalities.